The componential analysis of literary meaning - Belfarhi, Khadija (Colombian Applied Linguistics Journal, 2013)
The present paper aims at showing the importance of understanding English literary texts via the semantic analysis. Understanding literature as being a specific and more or less decompostional language is to rely on a lexico-semantic interaction which establishes meaning from different relations between words’ components because the latter hold meaning not clearly seen in the words of the text. The semantic analysis of literary texts enables the reader to establish a network of relations between terms and settles on a meaning that other semantic theories may not reach. This research provides a semantic analysis based on the lexical decomposition of the word into major and minor components whose semantic interaction yields meaning systematically. The application of the componential analysis on English literary texts can establish a lexical interaction based on semantic interrelations between words at the deep level because the minor components are not seen at the surface level. The interrelations between components can therefore yield the meaning enclosed at the surface level. The componential analysis is a way to getting into the deep surface structure of words through establishing semantic interrelations between words. This task enables the reader to find meaning in the possible components words may have, and makes him/her checking it by logical inference that stands primarily on the utterance as source of meaning projection.